Implementasi Corporate Social Responsibility (CSR) Di PT Trimitra Lestari Kabupaten Tanjung Jabung Barat (Suatu Tinjauan Etika Bisnis Islam) - Alliful Bastomi; Addiarrahman Addiarrahman; Anzu Elvia Zahara (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
Corporate Social Responsibility (CSR) is a company's commitment to contribute to sustainable economic development, by paying attention to corporate social responsibility and emphasizing a balance between attention to economic, social and environmental aspects. This research uses qualitative methods. The data used are primary and secondary data. Data were obtained by observation, interview and documentation methods. The object of this research is the community of Purwodadi Village, Tebing Tinggi District, West Tanjung Jabung District. Based on the results of the study shows that, the Corporate Social Responsibility (CSR) program of PT. Trimitra Lestari has been running quite well and providing benefits to the community around the company. In the review of Islamic business ethics, the implementation of the Corporate Social Responsibility (CSR) program of PT. Trimitra Lestari is in accordance with the principles of Islamic business ethics. However, there are still several programs that need to be improved as explained by the community, where the community expects a Corporate Social Responsibility (CSR) program that can empower and prosper the community.